Comparative Analysis of Characteristic Parameters of Supercritical Water-Cooled Reactor and Molten Salt Reactor - Pingxun ZHANG; Bo LIU; Xiaoze ZHAO (南方能源建设)
[Objective] The concept designs of the six types of reactors, proposed by the Generation Ⅳ International Forum (GIF), aim to significantly reduce the generation of nuclear waste, fully utilize uranium resources, and lower the construction and operating costs of nuclear power. As candidate reactor types, supercritical water-cooled reactors and molten salt reactors have garnered positive attention from various countries owing to their high safety, cleanliness, and efficiency advantages. In an effort to elucidate the future development trajectory of the fourth generation reactor, this paper summarizes the differences in the characteristic parameters between these two reactors, assesses the merits and drawbacks of diverse reactor types, and offers suggestions for their development. [Method] The development status of supercritical water-cooled reactors and molten salt reactors was introduced, both domestically and internationally. Comparisons and analyses of the differences between the two reactor types were conducted in terms of safety, material preparation, system design, nuclear fuel, etc., and deep thoughts on the future development direction were formulated, with the hope of having promoted the further advancement of the fourth generation reactor. [Result] Both supercritical water-cooled reactors and molten salt reactors are currently working towards overcoming the R&D challenges associated with materials and systems. Additionally, each of these reactor types possesses its own distinctive characteristics in the realms of safety and nuclear fuel utilization. [Conclusion] In order to achieve the smooth development of the two types of reactors, it is necessary to combine existing technologies, strengthen international cooperation, and continuously innovate and develop. Should the commercial operation of the fourth generation reactor be deemed achievable at the earliest convenience, the supercritical water reactor can draw upon existing technical conditions to expedite project implementation. Conversely, if a longer-term development plan is prioritized, the merits of molten salt reactors, utilizing thorium-based and liquid nuclear fuel, would merit commensurate efforts from all nations.